The trilemma of Turkish techno-nationalism: Choosing between Washington, Brussels and Beijing - Çağdaş Üngör (Stiftung Wissenschaft und Politik (SWP), 2025)
Ankara's "techno-nationalist" policies aim to place Turkey among the innovation leaders of the 21st century. The country has already achieved notable progress in its defence industry, launched its own EV brand and is preparing a space mission. But creating "native and national" (yerli ve milli) alternatives to the big global players in artificial intelligence (AI), 5G or semiconductors is not an easy task. With few commercial success stories to show, Turkey still needs international partners to develop innovation in the twenty-first century. This is likely to become more challenging under the Trump administration, whose drastic trade policies have complicated the relationships between China, Europe and the United States. With different dependencies on each of these actors (American digital corporations, Chinese network infrastructure and EU tech norms) Turkey faces a geopolitical trilemma in the field of technology.
Keywords: 320; Turkey; President Erdoğan; AKP; innovation leader; defence industry; national arms industry; China; Europe; United States; Trump administration; 5G technology; robotics; artificial intelligence (AI); autonomous weapons systems